Primula bellidifolia King ex Hook.f. : A New Record for the Flora of Nepal - Thapa, Til Kumari; Chhetri, Rita; Eveleigh , Pam (Journal of Plant Resources, 2024)
Primula bellidifolia has been conformed to occur in Nepal.